Comorbidities and personal burden of urgency urinary incontinence: a systematic review. Issue 10 (20th September 2013) - Coyne, K. S.; Wein, A.; Nicholson, S.; Kvasz, M.; Chen, C.‐I.; Milsom, I.
Summary Aims Studies on the burden and comorbidities associated with urgency urinary incontinence (UUI) are difficult to compare, partly because of the evolution of definitions for lower urinary tract symptoms and the various instruments used to assess health‐related quality of life (HRQL). This article summarises published evidence on comorbidities and the personal burden associated specifically with UUI to provide clinicians with a clear perspective on the impact of UUI on patients. Methods A PubMed search was conducted using the terms: (urgency urinary incontinence OR urge incontinence OR mixed incontinence OR overactive bladder) AND (burden OR quality of life OR well‐being OR depression OR mental health OR sexual health OR comorbid), with limits for English‐language articles published between 1991 and 2011. Results Of 1364 identified articles, data from 70 retained articles indicate that UUI is a bothersome condition that has a marked negative impact on HRQL, with the severity of UUI a predictor of HRQL. UUI is significantly associated with falls in elderly individuals, depression, urinary tract infections, increased body mass index, diabetes and deaths. The burden of UUI appears to be greater than that of stress urinary incontinence or overactive bladder symptoms without UUI. UUI adversely impacts physical and mental health, sexual function and work productivity. Conclusions UUI is associated with numerous comorbid conditions and inflicts a substantial personal burden on many aspects of patients' lives. Healthcare providers should discuss UUI with patients and be aware of the impact of UUI and its associated comorbidities on patients' lives.